1986
DOI: 10.1007/bf00124875
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and eugenics: Singapore's population policies

Abstract: Singapore, after serving for two decades as a model for Third World birth control and economic development programs, is now abandoning its earlier population policies in favor of encouraging dramatic population growth. The initial eugenics-based program introduced in 1984 sought increased fertility for university-educated women and provided major subsidies for the voluntary sterilization of poor and uneducated parents. These much publicized and internationally discussed programs have now been abandoned in favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…In future research, it would be interesting to further investigate how the effects of the socioeconomic factors on the second-child fertility intention differ between migrants and other social groups in China. For instance, unlike the positive effect of home ownership on fertility intentions observed in many other countries (Chudnovskaya, 2019;Felson & Solaún, 1975;Mulder & Billari, 2010;Palen, 1986;Sobotka et al, 2011), the revealed negative effect of home ownership in China's floating population is worth further exploration. In particular, we should examine whether the competing effect between home ownership and childbearing is peculiar to China's floating population.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In future research, it would be interesting to further investigate how the effects of the socioeconomic factors on the second-child fertility intention differ between migrants and other social groups in China. For instance, unlike the positive effect of home ownership on fertility intentions observed in many other countries (Chudnovskaya, 2019;Felson & Solaún, 1975;Mulder & Billari, 2010;Palen, 1986;Sobotka et al, 2011), the revealed negative effect of home ownership in China's floating population is worth further exploration. In particular, we should examine whether the competing effect between home ownership and childbearing is peculiar to China's floating population.…”
Section: Discussionmentioning
confidence: 94%
“…Home ownership provides housing security and has symbolic values and thus may be seen as an essential step prior to childbearing (Chudnovskaya, 2019). It has long been considered a fertility incentive (Felson & Solaún, 1975;Palen, 1986).…”
Section: Home Ownership and Fertility Intentions Among China's Floamentioning
confidence: 99%
“…With these two beliefs, SDU was established to offer opportunities for single graduate men and women to meet in social settings. The PAP government justified the exclusion of non-graduates by arguing that they had no problems finding marriage partners (Straits Times, 7 March 1985; see also Palen, 1986).…”
Section: T Chongmentioning
confidence: 97%
“…The Board introduced a range of incentives and controls, collectively known as the ''Stop at Two'' policy, to reduce the fertility rate. Several authors have catalogued these measures (e.g., Graham 1995;Palen 1986;Teo and Yeoh 1999). They included:…”
Section: Government Policy On Nuclear Familiesmentioning
confidence: 99%